The Comparative Efficacy of Conventional Short-Stretch Multilayer Bandages and Velcro Adjustable Compression Wraps in Active Treatment Phase of Patients with Lower Limb Lymphedema - Borman, Pinar; Koyuncu, Esra G; Yaman, Ayşegül; Calp, Emel; Koç, Funda; Sargut, Rüveyda; Karahan, Sevilay (Mary Ann Liebert Inc, 2021)
Background: Compression is the most important component of complete decongestive therapy (CDT), but there is no standard best method for applying compression. The aim of this study was to evaluate the comparative efficacy of conventional multilayer short-stretch bandaging, and a velcro adjustable compression wrap with regard to volume reduction, ultrasonographic measurements, functional-status, and quality of life (QoL) in the active CDT period of patients with lower limb lymphedema. Methods and Results: The demographic and clinical variables of lower limb lymphedema patients were recorded. All patients received skin care education, manual lymphatic drainage, and supervised lyphedema exercises, and were randomly allocated to Group1 (multilayer short-stretch bandaging-Rosidal-K®) or to Group 2 (adjustable-compression-velcro-wrap-Circaid Reduction-kit®) for a duration of 3 weeks with 15 sessions. Limb volumes were assessed by perometer. Ultrasonographic measurements included subcutaneous soft tissue thickness. The functional disability and QoL were evaluated by the Lower Extremity Functional Scale and LYMQOL-Leg (Lymphedema Quality of Life Questionnaire-Leg), respectively, at baseline, after CDT, and at first-month follow-up. Thirty-six patients (10 male and 26 female) with mean age of 51.6 ± 11.7 years were included. Fourteen patients had primary and 22 patients had secondary lymphedema. The median duration of lymphedema was 68 months. Significant improvements in volumes and ultrasonographic measurments were observed in both groups at the end of therapies, and improvements sustained up to a month. Appearance, symptoms, and overall QoL-subscores were improved only in Group 2. Conclusion: In conclusion, adjustable compression velcro-wrap performed as a part of CDT can greatly reduce the volume similiar to conventional multilayer bandages, as well as improve the QoL. It can be a comfortable alternative to the conventional multilayer bandages in the active treatment phase of the CDT.
Keywords: Male; Treatment Outcome; Lower Extremity; Compression Bandages; Quality of Life; Humans; Female; Lymphedema; Child; 3. Good health